Cross my heart [compact disc, unabridged] - Patterson, James, 1947- (Patterson, James, 1947- Alex Cross series., 2013)
Detective Alex Cross is a family man at heart. Nothing matters more to him than his children, his grandmother, and his wife Bree. His love of his family is his anchor, and gives him the strength to confront evil in his work. One man knows this deeply, and uses Alex's strength as a weapon against him.